International Symposium for Intelligent Transportation and Smart City (ITASC) 2019 Proceedings : Branch of ISADS (The International Symposium on Autonomous Decentralized Systems) /: Branch of ISADS (The International Symposium on Autonomous Decentralized Systems). (2019) - Unknown
No abstract available